2005
DOI: 10.1016/j.febslet.2005.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus‐stabilizing activity of artificial VLDL‐receptor variants defines a new mechanism for virus neutralization by soluble receptors

Abstract: Members of the low-density lipoprotein receptor family possess various numbers of ligand binding repeats that nonequally contribute to binding of minor group human rhinoviruses. Using an artificial concatemer of five copies of repeat 3 of the human very-low density lipoprotein receptor, we demonstrate protection of HRV2 against low-pH mediated uncoating and inhibition of penetration of an RNA-specific fluorescent dye into the intact virion. This indicates that the recombinant receptor inhibits viral breathing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…Apparently, in the absence of the ␤-propeller domain the high-avidity attachment of the receptor via several ligand-binding modules stabilizes the native conformation of the virus. This is in line with earlier data of Nicodemou et al (32), who demonstrated stabilization of HRV2 by the soluble concatemeric pentamer of module 3 (V33333) of VLDLR in vitro. Stabilization by WIN-52084 and the ␤-propeller negative receptor were additive, shifting the sigmoid curve even more toward lower pH values (Fig.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Apparently, in the absence of the ␤-propeller domain the high-avidity attachment of the receptor via several ligand-binding modules stabilizes the native conformation of the virus. This is in line with earlier data of Nicodemou et al (32), who demonstrated stabilization of HRV2 by the soluble concatemeric pentamer of module 3 (V33333) of VLDLR in vitro. Stabilization by WIN-52084 and the ␤-propeller negative receptor were additive, shifting the sigmoid curve even more toward lower pH values (Fig.…”
Section: Resultssupporting
confidence: 82%
“…As a consequence of ␤-propeller deletion, the infection was delayed and less efficient. Stabilization of HRV2 by a receptor construct carrying five copies of V3, the third module of VLDLR arranged in tandem, has been noted earlier (32). This effect is most probably due to the strong multivalent attachment of the receptor modules around the fivefold axes of icosahedral symmetry (36).…”
Section: Discussionmentioning
confidence: 88%
“…Nanocontainers purified by spin SEC were decorated with His 6 -tagged MBP-V33333 via the DOGS-NTA incorporated into the lipid membrane to allow for subsequent HRV2 binding (nanocontainer/receptor/virus [NCϩRϩV] complexes). Since the multivalent receptor impedes movements of the capsid proteins with respect to each other (19,29), HRV2-receptor complexes require a lower pH for conversion into subviral particles than free virus. Therefore, in order to keep the concentration of free receptor low (to avoid formation of virus-receptor complexes in solution), it was used at a molar ratio of about 0.01 with respect to Ni 2ϩ -NTA groups (assuming that 50% of the NTA groups are found on the inner leaflet).…”
Section: Resultsmentioning
confidence: 99%
“…Under the same conditions, but using liposomes without receptor, similar leakage effects were observed (data not shown). As stated above, the lack of a stimulating effect of the receptor might be explained by the multivalent nature of the binding impeding movements of viral capsid proteins with respect to each other (29), thus inhibiting the structural changes necessary for exposure of amphipathic domains. The stabilization of the virus might thus counteract the virus-concentrating effect of the receptor and explain the Ϫ6 (Ͻ10 virions/ nanocontainer); at higher ratios the cDNA signal decreases again.…”
Section: ϫ5mentioning
confidence: 99%
“…At least in the case of minor group HRVs, it cannot be explained by a "catalytic" function of the receptor; binding of a very-low density lipoprotein receptor mimetic, a head-to-tail concatemer of ligand-binding repeat V3 that exhibits high affinity for HRV-A2 (61) stabilizes the virus rather than aiding in its conversion to A-particles (62). This is dissimilar to major group viruses which are uncoated by an excess of soluble ICAM-1 alone (63).…”
Section: Discussionmentioning
confidence: 99%